Inflammatory immune mediators and Plasmodium falciparum infection: a cross-sectional study among Sudanese patients with severe and uncomplicated malaria - Dia Aldeen Alfaki; Mohajir Hussein; Mustafa Hassan; Amanda G. Eloraish; Mohamed Mubarak Elbasheir (Exploration of Immunology, 2023)
Aim: A number of questions remain unanswered concerning how infected individuals regulate their immune response to Plasmodium falciparum (P. falciparum) parasites at varying levels of exposure. Due to the interactions of inflammatory mediators and cytokines with the P. falciparum parasite complex density, several mediators influence parasitaemia and may give some indications of disease severity and represent effective signs in clinical manifestations of malaria disease. Methods: In this study, various levels of immune response mediators of interleukin 8 (IL-8), tumor necrosis factor-beta (TNF-β, also known as lymphotoxin-α), interferon-gamma (IFN-γ), IL-6, and IL-10 were investigated to the different phases of infection with P. falciparum in hyperendemic states in Sudan (White Nile, Blue Nile). This study vetted the association between certain inflammatory mediators during malaria infection and parasite density. This study was based on a total of 108 cases, in which 86 patients (62.0%) were uncomplicated and (17.6%) were severe, all met the diagnostic criteria and were clinically admitted for malaria infections. Commercial enzyme-linked immunosorbent assay (ELISA) kits were employed to determine the inflammatory mediator’s serum concentration. Results: The analysis of data indicated that older infected children had substantially raised levels of IFN-γ (P < 0.05), among study groups, levels of IFN-γ, TNF-β, and IL-8 were strongly linked with the severity of malaria, in severe and uncomplicated cases (P < 0.001), IL-6 and IL-10 were significantly associated with severe malaria cases uniquely (P < 0.001). Furthermore, we reported a positive correlation between IL-8 and TNF-β during all infection cases (r = 0.760, P < 0.001). Additionally, in severe malaria cases IL-6 was positively correlated with IL-10 (r = 0.575, P = 0.010). Conclusions: Eliminating P. falciparum blood-stage infection needs effective, specific, and tuned immune response strategies, which may present in the mediator’s correlations and depend on the density of the infection. Besides the effective levels contribution of certain cytokines that play protective roles during different stages of an infection.